A dialectical methodology applied to medical education in a Primary Care syllabus - Amendola, Fernanda; Veiga Martines, Wânia Regina; Uchoa Nawa Pagotto, Mayumi; Gonzalez Manso, Maria Elisa (O Mundo da Saúde, 2013)
The essay aims at making public the pedagogical knowledge on the education of undergraduate medical students in the City of São Paulo, Brazil, in Primary Care. Proposals and objectives of the academic syllabus “Integration between University, Practical Work and Community” (Integração Academia, Serviço e Comunidade) are dialectically described in order to allow medical undergraduate students to fully experience both the practical and the theoretical contents which are the guiding principles of the Brazilian Unified Health System (Sistema Único de Saúde, acronym SUS), the Family Health Strategy and the Family and Healthcare Medicine. Syncresis (preparation to gather knowledge), analysis (knowledge construction) and synthesis (knowledge elaboration) come together to contribute for streamlining the teaching practice and to provide the medical undergraduate students an expanded and critical view on the health-disease process in view of the current structure of Primary Care in Brazil.